Identifikasi Kecukupan Tata Kelola Sampah Di Kawasan Malioboro - Budiman, Yosef Satrianus; Taslim, Syafaat; Ariyogi, M. Iksan (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
This study investigates the need for sustainable waste management in the Malioboro area of Yogyakarta city. Because the accuracy of perspective, approach, program choice, and technical implementation as well as support capacity in the field that has not been maximized, management needs to be reviewed. There are only 6 cleaning staff prepared by UPT Malioboro with limited working time. In this research, the method used is descriptive quantitative rationalistic method. The rationalistic approach is the process of testing the truth not only through sensual empiricism (measured by the senses) but continued through the meaning of sensual empiricism, logical empiricism (thinking) and mental empiricism (ethics). Sensual empirical, empirical logic, and empirical ethics and based on theoretical basis are used to extract data, interpret behavior, perform data analysis, present findings and discuss (meaning the findings).